Sikap dan Pengetahuan Pengunjung Warung Kopi dengan Kepatuhan Penggunaan Masker Pada Masa Pandemi Covid-19 - Sarifudin Andi Latif; La Ode Swardin; Asrianto La Ode (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; Most of the Covid-19 deaths in this outbreak were caused by comorbid or comorbid diseases such as hypertension, diabetes mellitus, coronary heart disease, and cerebrovascular disease. Purpose; knowing the relationship between the attitudes and knowledge of coffee shop visitors with compliance with the use of masks during the Covid-19 pandemic. Method; this type of descriptive research using a cross-sectional study design. The sampling technique used was accidental sampling as well as by using a questionnaire. Results; show attitude with a p-value of 0.000 and knowledge p-value of 0.000. Conclusion; that there is an influence on the attitude and knowledge of coffee shop visitors with compliance with the use of masks during the Covid-19 pandemic. recommendations for coffee shop owners to continue to provide instructions such as announcements in the form of pamphlets and provide a place to wash hands, as well as provide the distance for visitors when sitting to reduce the spread of Covid-19